Եկեղեցու մասին ուսմունքը հայ մատենագրության մեջ (Է.-Ը. դարեր) - Խմբ.՝ Առաքել Առաքելյան (1944-1948); Լևոն Կիսիբեկյան (1948-1950); Աշոտ Աբրահամյան (1950-1955); Առաքել Առաքելյան (1955-1956); Արթուն Հատիտյան (1956-1982); Պարգեւ Շահբազյան (1983-1984); Երվանդ Մելքոնյան (1985-1993); Տ. Ասողիկ եպս. Արիստակեսյան (1994-1996); Տ. Բագրատ աբղ. Գալստյան (1996-1998); Մարիամ Վարդանյան (պաշտոնակատար) (1998-1999); Տ. Արշակ աբղ. Խաչատրյան (պաշտոնակատար) (1999); Անդրանիկ Զեյթունյան (2000-2001); et al. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
У армянских церковных авторов VII-VIII веков было довольно развитое экклезиологическое мышление. Они создали и развили довольно когерентное учение о Церкви. Всесторонне используя классические богословские традиции,они раскрывают идею об основании Церкви до акта творения. Они показывают,что Церковь как таинство существовала в промысле Божьем еще до создания мира. The Armenian ecclesiastical authors o f the 7-8th centuries possessed a considerably developed ecclesiological consciousness and developed a rather comprehensive ecclesiological teaching. Relying on the classical Christian traditional thinking, they give prominence to the concept o f the pre-creation foundation o f the Church, showing that Church as a mystery existed in the providential design o f God prior to the creation o f the cosmos.
Keywords: Christianity; Armenian church